Novel Electrochemical Treatment of Spent Caustic from the Hydrocarbon Industry Using Ti/BDD - Alejandro Medel; Erika Méndez; José L. Hernández-López; José A. Ramírez; Jesús Cárdenas; Roberto F. Frausto; Luis A. Godínez; Erika Bustos; Yunny Meas (International Journal of Photoenergy)
During the crude oil refining process, NaOH solutions are used to remove H2S, H2Saq, and sulfur compounds from different hydrocarbon streams. The residues obtained are called “spent caustics.” These residues can be mixed with those obtained in other processes, adding to its chemical composition naphthenic acids and phenolic compounds, resulting in one of the most dangerous industrial residues. In this study, the use of electrochemical technology (ET), using BDD with Ti as substrate (Ti/BDD), is evaluated in electrolysis of spent caustic mixtures, obtained through individual samples from different refineries. In this way, the Ti/BDD’s capability of carrying out the electrochemical destruction of spent caustics in an acidic medium is evaluated having as key process a chemical pretreatment phase. The potential production of •OHs, as the main reactive oxygen species electrogenerated over Ti/BDD surface, was evaluated in HCl and H2SO4 through fluorescence spectroscopy, demonstrating the reaction medium’s influence on its production. The results show that the hydrocarbon industry spent caustics can be mineralized to CO2 and water, driving the use of ET and of the Ti/BDD to solve a real problem, whose potential and negative impact on the environment and on human health is and has been the environmental agencies’ main focus.